Propuestas para incrementar la recaudación tributaria - Adriazola Burga, Alexa (2021)
The author puts forward five proposals in order to shorten the economic and social gap that exists in Peru —represented by the access to public and private services— by increasing the number of taxpayers, and thus tax collection, in order to obtain a higher quantity and quality of public services. Therefore, confidence would be generated in Peruvian citizens towards the Government and a tax culture that gradually increases tax collection would be created.